Nonlinear equations with essentially infinite-dimensional differential operators - Bogdanskii, Yu. V.; Statkevych, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We consider nonlinear differential equations and boundary-value problems with essentially infinite-dimensional operators (of the Laplace–Lévy type). An analog of the Picard theorem is proved.